The Right to Life Based on Human Rights Principles: A Normative Study of the Death Penalty in Indonesia - Doortje Durin Turangan; Emma V.T. Senewe; Wempie Jh. Kumendong; Jemmy Sondakh (Journal of the Community Development in Asia (JCDA), 2021)
The right to life is the absolute right of every person and is included in the category of rights that cannot be reduced. Indonesia is one of the countries that still maintains and recognizes the legality of the death penalty as a way to punish the perpetrators of certain criminal acts such as narcotics, terrorism, and murder crimes despite the pros and cons. This study aims to investigate the regulation of the right to life against the death penalty in Indonesia, the construction of the death penalty law from human rights viewpoint, and the judge's consideration in imposing the death penalty associated with the principles of human rights. This study used a qualitative normative juridical approach by referring to the legal norms in statutory regulations and norms of the society. The findings highlight that the early existence of the death penalty in Indonesia is legally regulated in the Criminal Code, most of which are from the Netherlands, namely WvS (Wetboek van Strafrecht).